Book Reviews (Historia, 2021)
1. B.J. Liebenberg. Andries Retoriw in Natal2. Geyser (red.). BJ . Vorster - Select Speeches3. D . Picton.Seymore. VictorMn Buildings in South Africa4. S . Welz. Cape Silver B Silversmiths 5. Lesley & Stephen Townsend. Bokaap Faces and Facades6. M . Miszewski. The Quality of Life7. C . Pama. Bowler's Cape Town8. Marielise Botha. Herkoms van die Kaapse stoele9. A.H. Smith. Treasures of the Africana Museum10. D . Bax. Het ouhte Kaapse zilver11. Gerhardt Jooste. Diensherinneringe12. F.W. STrydom. Die Swart Verskrikking13. Philip Bateman. Generals of the Anglo-Boer War14. E.P. Mathers. Zambesia - England's El Dorado 15. R.L. Cope (ed.), The Journals ls of the Rev . T.L. Hodgson16. A . W . Hodson. Trekking the Great Thirst17. B W . . Clapp (ed.). England since 1760 a . B . Brain) .